HUBUNGAN PENGEMBANGAN DIRI DENGAN LOYALITAS KINERJA GURU SEKOLAH DASAR - Puji Astuti (Perspektif Ilmu Pendidikan, 2019)
This research aims to determine the correlation between self-development and teacher performance loyalty. This study was conducted in SDN 2 Margomulyo, OKU Timur with a total of 25 teachers. A cross-sectional design was used and implemented from April to August 2018. The data analysis technique used was nonparametric statistics. The results showed that there was no signifcant relationship between self-development with performance loyalty (0,877 > 0,05). Based on this result, implications and recommendations are discussed further.